Social Media Content and Credibility (Situation analysis of news shared on Facebook by Journalists from Nepal) - Paudel, Ganesh K. (Bouddhik Abhiyan (बौद्धिक अभियान), 2022)
The qualitative research is conducted using status exploration and structured interviews of civil society members and has studied the credibility of messages posted on Facebook by journalists. Survey has observed 749 Facebook statuses for February, March, and July of 2020 posted by various Journalists working from Sunsari District. The journalists are selected using a systematic random sampling method. Posts are observed on the basis of Fact, Attribution of authentic sources, Balance in coverage, clarity in message etc. The content analysis shows Journalists are conscious of their responsibility towards society and do post factual information on social media however they sometimes make mix-ups of news and opinion. Some journalists post sensational information to increase their viewership but that has decreased their credibility. Civil society members and information users’ perspectives pointed out that people follow the Facebook posts of journalists for news updates, however, they verify it with other credible journalists and or trusted mainstream media. Journalists share information using Facebook however fact-checking and balance seem lacking. To understand social media content media literacy is necessary.